Advanced Research on Computer Science and Information Engineering International Conference, CSIE 2011, Zhengzhou, China, May 21-22, 2011, Proceedings, Part II - Shen, Gang.; Huang, Xiong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This two-volume set (CCIS 152 and CCIS 153) constitutes the refereed proceedings of the International Conference on Computer Science and Information Engineering, CSIE 2011, held in Zhengzhou, China, in May 2011. The 159 revised full papers presented in both volumes were carefully reviewed and selected from a large number of submissions. The papers present original research results that are broadly relevant to the theory and applications of Computer Science and Information Engineering and address a wide variety of topics such as algorithms, automation, artificial intelligence, bioinformatics, computer networks, computer security, computer vision, modeling and simulation, databases, data mining, e-learning, e-commerce, e-business, image processing, knowledge management, multimedia, mobile computing, natural computing, open and innovative education, pattern recognition, parallel computing, robotics, wireless networks, and Web applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Software Engineering